The Interplays between Government, Human Security and Geopolitics in Indonesia's Governance of Afghan Refugees, Human Security Perspective - Mohammad Rafi Hamidi; Ali Maksum; Sabza Gol Qaderi (Universitas Gadjah Mada, 2025)
Traditional approach on security has emphasized on the issues of border and sovereignty of states. This paper examines the complex interplay between governance, human security and geopolitical transformations in the context of forced migration, focusing on the experience of Afghan refugees in Indonesia after 2021. The research argues that Indonesia’s “informal” governance approach, in the absence of a domestic legal framework, has placed refugees in a prolonged state of “limbo”. This situation has directly impacted on various dimensions of their human security, including economic, social and psychological security. Using content analysis and case study methods, this article shows that the Taliban’s takeover of Afghanistan in 2021, as a geopolitical trigger, has exacerbated existing challenges and fueled multiple insecurities for refugees. The findings emphasize that relying solely on international cooperation is not enough and that countries need to establish a domestic legal framework to provide effective governance based on human dignity. Finally, this article emphasizes the importance of adopting a comprehensive human security approach to managing refugee crises and offers suggestions for policymakers in Indonesia and other host countries.